Pinwheel-Shaped Titanium Plates Should Be Fixed to the Skull Using All Screw Holes to Protect the Plates from Being Bent - Shoko Merrit Yamada; Katsuya Gorai; Koichi Gonda (Case Reports in Surgery)
Introduction. In cranioplasty, pinwheel-shaped titanium mini plates are frequently used to cover bone defects produced by burr holes, and it is common to insert screws through only a few of the holes in cranial flap fixation. Presentation of Case. A 69-year-old man who had undergone clipping surgery for subarachnoid hemorrhage 16 years previously visited our clinic because a titanium plate had penetrated his scalp one month after he was hit on the head by a wall cabinet. Imaging studies revealed that part of the titanium plate had bent outwards and penetrated the skin. The plate was surgically removed, a relief skin incision was made 6 cm posterior to the skin defect to suture the defected portion without causing tension, and a skin graft was applied to the relief skin incision portion. Two months after the maneuver, the skin graft had been successfully incorporated without infection. Discussion. Even after the subcutaneous and the cutaneous tissue have completely covered the pinwheel-shaped titanium mini plate, an edge without screw fixation can be easily bent by a hard blow to the overlying scalp. We recommend fixation of pinwheel-shaped titanium plates used in cranioplasty through all screw holes to protect against the plate being bent.